Combined Use of Enhanced Coefficient Adjustment Technique and Module-based Substitution to Hide Secret Message in ECG Signal - Ching-Yu, Yang; Tsung-Hsiang, Hsu; Pei-Yun, Chen (European Journal of Applied Sciences, 2023)
We present an effective electrocardiogram (ECG) steganography technique for concealing patient’s diagnosis and sensitive information within ECG signals. The method utilizes the enhanced coefficient adjustment technique (ECAT) and module-based substitution to embed a large number of secret bits into an ECG host. The proposed method consists of two stages. In stage I, ECAT attempts to embed (n − 1) bits in a host bundle with the size of 1 * (n - 1) if the first decision rule is satisfied; otherwise, the number of bits L1 is embedded in the bundle by Mod u. In stage II, if the second rule is true, then the next input (n − 1) bits are hidden into the bundle with the size of 1 * n by ECAT; otherwise, data bits in length of L2 are embedded in the bundle by Mod u. Simulations demonstrate that the payload and signal-to-noise ratio (SNR) of our method surpass those of existing methods. Additionally, our method ensures good perceived quality and offers protection against attacks. The proposed method finds application in biometric measurements, including portable healthcare devices and IoT-based health monitoring systems.